PAUCITY OF INTRAHEPATIC BILE DUCTS - O. E. Iryshkin; I. M. Iljinsky; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов, 2013)
The paucity of intrahepatic bile ducts is characterized by reducing the quantity of interlobular bile ducts in re- lation to portal tracts of the liver. There are two defined forms of paucity of intrahepaticbile ducts: syndromatic, which is associated with various extrahepatic abnormalities and nonsyndromatic, being the heterogeneous group of disorders, including congenital infections, metabolic, endocrine, immune disorders, congenital infections and various other disorders. In many instances paucity of intrahepatic bile ducts remains idiopathic. The review contains terminological issues, the description of the classification and the morphological characteristic, the dif- ferences of syndromatic and nonsyndromatic forms of paucity of intrahepatic bile ducts, and also the description of principles of differential diagnosis of paucity of intrahepatic bile ducts and biliary atresia.